ANALISIS FRAMING TERKAIT KEBIJAKAN INOVASI DAERAH DI PROVINSI SULAWESI TENGGARA - Indra Rahayu Setiawati; Maudhy Satyadharma; Djoni Tepu; Kemal Jusra; La Ode Muhammad Ichwan Sjachrawy (Pojok Publisher, 2025)
This study analyzes the framing of news related to regional innovation policies in Southeast Sulawesi Province. Using Robert M. Entman's framing model, this study identifies how the media frames problems, causes, moral judgments, and recommended solutions for various regional innovation initiatives. The results of the analysis show that in terms of problem definition, the media highlights that regional development requires a renewed perspective and a technology-based approach and collaboration. In terms of cause diagnosis, the media identifies the main causes of the issues raised as old (conventional) patterns and low capacity, both in terms of human resources, technology, and inter-institutional coordination. In terms of making moral judgment, the media conveys a positive moral assessment of innovative efforts that are being or have been carried out by the regional government or related institutions. In terms of treatment recommendations, the media suggests a collaborative, data- and technology-based approach, as well as strengthening human resource capacity. The application of technology (both in agriculture and transportation), strengthening synergy between regions (agglomeration), industrial downstreaming, and integration between the government and the private sector are the common threads of all suggested solutions.